Positive Interval Observer-based State Feedback Controller for Uncertain General Anaesthesia System - Jing Jing Chang; S. Syafiie (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The drug delivery process of general anaesthesia in the human body is most commonly described by the Pharmacokinetic/Pharmacodynamic (PK/PD) model. Since the PK model is a positive linear system, the design of the controller can be treated as a positive stabilization problem. In this paper, a state feedback controller with positive interval observer was designed using a linear programming approach by taking into account the inter-individual variability among patient in the PK model. The designed controller was assessed by simulation on a pool of patients. The result shows that the design of a fix controller for the whole population is difficult due to the conflict between performance and robustness.